2020
DOI: 10.15544/mts.2019.42
|View full text |Cite
|
Sign up to set email alerts
|

Differences of Consumer Behaviour Regarding Plastic Usage

Abstract: The growth of plastic packaging waste and the need to manage it determine the relevance of this research. The problem is the lack of information about consumers' behavior regarding usage and wastage of plastic packaging in certain groups according to age, gender, incomes, and education in Lithuania. The purpose of the research is to investigate consumer behavior in the purchase process regarding the choice of plastic usage. Quantitative sampling was used to gather data from 641 respondentconsumers who regularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…In addition, those with bachelor's degrees displayed a greater tendency to use medium-use and long-use plastics. These results were opposite to Jeżewska-Zychowicz and Jeznach (2015) as well as Jesevičiūtė-Ufartienė (2019), who found that people with higher educational attainment possess heightened environmental awareness and are more inclined to minimize their usage of plastic packaging [26,38]. However, this study corroborated the findings of Afroz et al (2017) and Madigele et al (2017), which revealed that knowledge and environmental behavior are not necessarily interconnected [39,40].…”
Section: Plastic Consumption Behaviorscontrasting
confidence: 69%
See 4 more Smart Citations
“…In addition, those with bachelor's degrees displayed a greater tendency to use medium-use and long-use plastics. These results were opposite to Jeżewska-Zychowicz and Jeznach (2015) as well as Jesevičiūtė-Ufartienė (2019), who found that people with higher educational attainment possess heightened environmental awareness and are more inclined to minimize their usage of plastic packaging [26,38]. However, this study corroborated the findings of Afroz et al (2017) and Madigele et al (2017), which revealed that knowledge and environmental behavior are not necessarily interconnected [39,40].…”
Section: Plastic Consumption Behaviorscontrasting
confidence: 69%
“…Single-use plastics were found to be consumed at high rates across almost all family income levels. Previous research has found that family income influences plastic consumption behavior, but the findings are diverse [26,29,39,40]. For instance, Jeseviči ūt ė-Ufartien ė (2019) [26] and Afroz et al (2017) [39] reported that people with higher incomes were less willing to pay for plastic products because they spent money more conscientiously.…”
Section: Plastic Consumption Behaviorsmentioning
confidence: 99%
See 3 more Smart Citations